Femoral Metastasis from Penile Carcinoma: Report of 2 Cases - Laura Braumann; Panagiotis Tsagozis; Rikard Wedin; Otte Brosjö (Case Reports in Urology)
Purpose. Penile cancer rarely gives symptomatic skeletal metastases. Methods. We present 2 patients with squamous carcinoma of the penis who were surgically treated for metastases in the femur. Results. Both patients had pathological fractures and were operated on. In one case, the skeletal metastasis preceded any lymphatic spread of the disease, suggesting early haematogenous dissemination. Conclusions. Endoprosthetic reconstruction resulted in pain relief and restored the ambulatory capacity. Clinicians should be aware of the possibility for symptomatic bone metastases with a risk for pathological fracture in patients with penile cancer.